Efficacy and safety of the combination of propofol and S(+)-ketamine for procedural sedation in pediatric patients undergoing totally implantable venous access port implantation: A prospective randomized controlled study - Zhang, Yingjun; Ou, Chaopeng; Bai, Xiaohui; Lai, Jielan; Huang, Wan; Ouyang, Handong (Frontiers in Pediatrics, 2022)
Background: Totally implantable venous access port (TIVAP) implantation is usually performed under general anesthesia with endotracheal intubation in children. Procedural sedation without endotracheal intubation has been applied to minor pediatric surgeries like central venous catheter insertion. To explore a more efficient and less invasive anesthesia mode to implant TIVAPs for children, we aimed to evaluate the efficacy and safety of procedural sedation using propofol and S(+)-ketamine compared with general anesthesia. Methods: Sixty-six patients aged 6 months to 10 years undergoing TIVAP implantation were randomly allocated to two groups. Patients under procedural sedation [S(+)-ketamine-propofol (sketofol) group] were given target-controlled infusion of propofol 4μg/ml using the Paedfusor model and S(+)-ketamine 0.5mg/kg as induction, and had target-controlled infusion of propofol 3-4μg/ml as maintenance. Patients in sketofol group received medium-flow oxygen inhalation through facemasks during surgery. Patients under general anesthesia (control group) were given propofol 2mg/kg, cisatracurium 0.2mg/kg, fentanyl 3μg/kg as induction, and sevoflurane 0.8 minimum alveolar concentration as maintenance after endotracheal intubation. Primary outcome was the postoperative emergence agitation evaluated 5 min after awakening. Results: Postoperative emergence agitation evaluated 5 min after awakening was lower in sketofol group versus control group (1.0 [0.5, 1.0] vs 3.0 [2.0, 4.0]; median difference [95% CI]: 2.0 [1.0, 2.0]; P<0.001). Time to awakening was significantly lower in sketofol group versus control group (15.0 [5.0, 23.0] vs 26.0 [20.5, 37.5]; median difference [95% CI]: 11.0 [7.0, 19.0]; P<0.001), as well as time to discharge from post anesthesia care unit (35.0 [24.0, 45.0] vs 45.0 [37.5, 59.5]; median difference [95% CI]: 10.0 [10.0, 23.0]; P<0.001). Postoperative complications or adverse events were not reported in sketofol group. Conclusions: Compared to general anesthesia with endotracheal intubation, procedural sedation using propofol and S(+)-ketamine improves the postoperative emergence agitation right after the recovery of consciousness, and has advantage in shortening anesthetic recovery time for pediatric patients undergoing TIVAP implantation.